The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1590/s1806-92902016000400004
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid profile, meat quality, and carcass traits of Nellore young bulls fed different sources of forage in high-concentrate diets with crude glycerin

Abstract: -The objectives of this study were to evaluate the effect of forages with different nutritional valuesspecifically, corn silage (CS), sugar cane (SC), and sugar cane bagasse (SB) -in diets with crude glycerin, on carcass traits, meat quality, and fatty acid profile, using young Nellore bulls finished in the feedlot. Thirty young Nellore bulls with an initial average body weight of 416.70±24.74 kg were randomly assigned to three treatments containing different sources of forage. The carcass traits and variables… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(6 citation statements)
references
References 42 publications
0
4
0
2
Order By: Relevance
“…Biodiesel by-products, which have become a relevant economic alternative replacing soybean meal and corn, have been tested for use in animal nutrition. Their effects on carcass traits and meat quality were evaluated when soybean meal were replaced by cakes from oilseeds such as cottonseed (Pereira et al, 2016) and sunflower cake (Oliveira et al, 2015), and also using glycerin replacing ground corn (Barros et al, 2015;Strada et al, 2015;Eiras et al, 2014;Ribeiro, Messana, José Neto, Fiorentini, & Berchielli, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Biodiesel by-products, which have become a relevant economic alternative replacing soybean meal and corn, have been tested for use in animal nutrition. Their effects on carcass traits and meat quality were evaluated when soybean meal were replaced by cakes from oilseeds such as cottonseed (Pereira et al, 2016) and sunflower cake (Oliveira et al, 2015), and also using glycerin replacing ground corn (Barros et al, 2015;Strada et al, 2015;Eiras et al, 2014;Ribeiro, Messana, José Neto, Fiorentini, & Berchielli, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The values of RFT (3 to 6 mm) met the requirements of the Brazilian beef industry. Other studies using CG in feedlot diets have reported similar RFT (Carvalho et al, 2014;Favaro et al, 2016;Ribeiro, Messana, Neto, Fiorentini, & Berchielli, 2016).…”
Section: Discussionmentioning
confidence: 60%
“…From the interpretation of first canonical correlation (i.e., between U 1 and V 1 ), our canonical loadings and cross-loadings suggest that an increase in SFT may enhance the intensity of red and yellow colors in beef cuts. Carotenoids, which strictly come from the diet in ruminants (Goodwin, 1992), are the main responsible for yellow color in bovine fatness (Dunne et al, 2009;Ribeiro et al, 2016). So, as meat fat is higher when fat thickness increases (Pflanzer and Felício, 2011), yellow (b*) intensity increases as fat thickness increases.…”
Section: Discussionmentioning
confidence: 99%
“…The pH was measured using a portable pH meter with a penetrating electrode (Fisherbrand TM , Göteborg -Sweden) introduced into the meat cut 2 to 4 cm depth (Dallantonia et al, 2015). The SFT measurements were taken along the ventral length of each meat cut using a Vernier digital caliper (Mitutoyo, Aurora, IL, USA; Ribeiro et al, 2016).…”
Section: Data Collectionmentioning
confidence: 99%